ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PETANI TERHADAP PRODUK REKAYASA GENETIKA - Guspri Devi Artanti; Hardinsyah Hardinsyah; Dewa Ketut Sadra Swastika; Retnaningsih Retnaningsih (Jurnal Gizi dan Pangan, 2010)
This cross sectional study was aimed at analyzing determinant factors of farmer’s acceptance on GMO Product. For these purpose 150 farmers was selected from Jombang District (East Java) and 150 rests was selected from Deli Serdang District (North Sumatera). A logistic regression was applied to analyze the determinant factors of farmer’s acceptance on GMO. The result showed that determinant factor of farmer’s acceptance was farmer’s knowledge on GMO. The higher level of knowledge, the lower the acceptance. The knowledge of farmer’s on GMO was different between the two areas. Another result of this study showed farmers expectation about GMO Food could be circulated it can give positive impact: high quality for their agriculture produce; increase the productivity of Indonesian agriculture; and more information and socialization about GMO Product from the government. The government preferably compiled the program to increase knowledge of the farmer’s against GMO by carrying out the approach and giving of information and the fact about GMO in the field through the increased in the activity of farmer’s involvement in the farmers group.